The problem of cognitive dissonance in translation and the ways of overcoming it - Raima, Shirinova; Bagini, Licia; Uljan, Qarshibaeva; Gulchehra, Qo‘shaeva (Linguistics and Culture Review, 2021)
In modern linguistics there is a considerable increase of the scientific works on cognitive aspect of the language and cognitive interpretation of the literary translation. The article discusses the cognitive dissonance phenomenon in literary translation and its role and importance in the study of cognitive dissonance and scientific research. The phenomenon of dissonance, consonance, and cognitive dissonance, and their linguistic meanings in different dictionaries have been looked through. At the same time, it is determined that cognitive dissonance is not only the object of modern linguistics and translatology but also the research in the field of music, economics, and information technology. The works of the foreign scientists as V.G.Voskoboynik, T.V.Drozdova, A.M.Kaplunenko, Y.S.Kimishnikova, S.V.Biyakova, O.A.Hopiyaynen, C.Gallen, R.Lemieux, E.G Miklos on cognitive dissonance and their conceptual methods have been studied as well. In particular, the cognitive dissonance phenomenon in the works translated from French into Uzbek and from Uzbek into French has been analyzed by examples. The phenomenon of cognitive dissonance is studied within an indirect translation frame, where realities are mixed up, and the unnecessary cognitive element is introduced to the text. Four ways, the translators may deal with the cognitive dissonance in the translation process, have been recommended.